A scoping review of echocardiographic and lung ultrasound biomarkers of bronchopulmonary dysplasia in preterm infants - Martini, Silvia; Corsini, Iuri; Corvaglia, Luigi; Suryawanshi, Pradeep; Chan, Belinda; Singh, Yogen (Frontiers in Pediatrics, 2023)
Despite recent improvements in neonatal care, moderate to severe bronchopulmonary dysplasia (BPD) is still associated with high mortality and with an increased risk of developing pulmonary hypertension (PH). This scoping review provides an updated overview of echocardiographic and lung ultrasound biomarkers associated with BPD and PH, and the parameters that may prognosticate their development and severity, which could be clinically helpful to undertake preventive strategies. A literature search for published clinical studies was conducted in PubMed using MeSH terms, free-text words, and their combinations obtained through appropriate Boolean operators. It was found that the echocardiography biomarkers for BPD, and especially those assessing right ventricular function, are reflective of the high pulmonary vascular resistance and PH, indicating a strong interplay between heart and lung pathophysiology; however, early assessment (e.g., during the first 1-2 weeks of life) may not successfully predict later BPD development. Lung ultrasound indicating poor lung aeration at day 7 after birth has been reported to be highly predictive of later development of BPD at 36 weeks’ postmenstrual age. Evidence of PH in BPD infants increases risk of mortality and long-term PH; hence, routine PH surveillance in all at risk preterm infants at 36 weeks, including an echocardiographic assessment, may provide useful information. Progress has been made in identifying the echocardiographic parameters on day 7 and 14 to predict later development of pulmonary hypertension. More studies on sonographic markers, and especially on echocardiographic parameters, are needed for the validation of the currently proposed parameters and the timing of assessment before recommendations can be made for the routine clinical practice.